Cambios en las dinámicas familiares de adolescentes en embarazo de la zona norte del municipio de Corozal - Sucre. - Galé Herrera, María Bernarda; Lucero Acosta, Niller Eylerth; Villalba Reyes, Viviana Del Carmen (Fundación Universitaria Claretiana, 2021)
102 páginas